Warm-season annual forage production systems in the semi-arid central Great Plains - Detter, Nicholas (My University, 2025)
The semi-arid Great Plains region has the highest concentration of beef cattle in North America, as well as a growing number of dairy cattle. This region, which stretches from the prairie provinces of Canada to the plains of Texas, is also experiencing declining aquifers for irrigation. This reduction in irrigation capacity creates the need for water-efficient forage-based cropping systems. Two studies were conducted in western Kansas to help improve the production of warm-season annual forages in the region. The first study evaluated the potential of summer annual legume species as more water-efficient alternatives to alfalfa, while retaining high forage nutritive value. This study sought to accomplish this by analyzing the viability, yield potential, nutritive value, water use efficiency, and economic returns of four summer annual legume species (cowpea [Vigna unguiculata], forage soybean [Glycine max (L.)], lablab [Lablab purpureus], and sunn hemp [Crotalaria juncea]) as well as two summer annual grass species (BMR forage sorghum [Sorghum bicolor (L.) Moench ] and pearl millet [Pennisetum glaucum]). This study was conducted in 2022 and 2023 at three locations: Garden City, KS (irrigated), Colby, KS (dryland), and Hays, KS (dryland). Grasses were generally higher yielding and had greater water use-efficiency (WUE) than legume species. Lablab and cowpea were the only two legume species that had good establishment. Cowpea and forage soybean had significantly greater crude protein concentration ([alpha] =0.05) than either of the grass species, and cowpea, forage soybean, and lablab all had significantly greater relative feed quality (RFQ) values ([alpha] =0.05) than either of the grass species. Economic returns in irrigated environments were lablab = BMR forage sorghum = forage soybean = cowpea ≥ pearl millet ≥ sunn hemp ([alpha] =0.05), and in dryland environments were lablab = cowpea ≥ BMR forage sorghum ≥ pearl millet = forage soybean = sunn hemp ([alpha] =0.05). A second study analyzed the effect that seeding rate had on four summer annual forage grasses: forage sorghum, sudangrass [Sorghum bicolor var. Sudanese], sorghum-sudan [Sorghum bicolor x S. bicolor var. Sudanese], and pearl millet. In 2022 and 2023, at Garden City, KS, and Hays, KS, four trials (two irrigated and two dryland) were conducted, where the above-listed species were planted at six different seeding rates, starting at 370,000 seeds ha⁻¹ and increasing by increments of 370,000 seeds ha⁻¹ to 2,220,000 seeds ha⁻¹. In 2024, at Garden City, KS, and Hays, KS, three additional trials (one irrigated and two dryland) were conducted for forage sorghum, which included seven seeding rates: 0.37 M, 0.74 M, 1.48 M, 2.22 M, 2.96 M, 3.7 M, and 4.44 M seeds ha⁻¹. Our results showed that seeding rate generally has a positive correlation with forage mass, with significant variation depending on the species and environment. We also established negative correlations between seeding rate and plant height, tillers per plant, stalk diameter, crude protein, and lignin concentration. Profitability varied greatly by species, seeding rate, and environment, with pearl millet consistently trailing the other three species due to generally lower yields. The findings of these studies will aid producers in the region as they integrate summer annual forages into their cropping systems by providing valuable information on the effects of crop choice and seeding rate on forage mass, forage quality, and profitability under both irrigated and dryland conditions.
Keywords: Summer annual forage; Semi-arid Great Plains; Seeding rate; Legumes; Forage economics; Western Kansas cropping systems